Strategi Sosialisasi Literasi Antikorupasi Berbasis Nilai Pancasila di SMA Negeri 07 Pekanbaru - Tirta Naila; Syafitri Syafitri; Ilham Hudi; Citra Aulia Restu; Yanita Deva; Rasita Nabila Filza; Febby Okta Valenda; Surya Deva (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
This service aims to create individuals who are not only educated about corruption but also committed to fighting the practice for the sake of the next generation of young people. This research uses the method of implementing counseling and anti-corruption literacy culture in SMA Negeri 07 Pekanbaru. There are three stages of the activity plan carried out, namely the first stage of preparation, which includes licensing, coordination, and socialization with SMA Negeri 07 Pekanbaru. The second stage, implementation, includes socialization and counseling. The third stage is the evaluation and preparation of activity reports. The results of socialization and counseling on anti-corruption literacy were carried out by conducting discussions and interviews regarding the understanding and application of Pancasila values and how the concept of corruption in the context of Pancasila shows a positive impact on students' understanding of corruption with Pancasila values so as to form an anti-corruption attitude and create a secular environment.